2019
DOI: 10.1161/jaha.119.011975
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cholesterol‐Uptake Capacity of HDL Might Promote Target‐Lesion Revascularization by Inducing Neoatherosclerosis After Stent Implantation

Abstract: Background We evaluated the importance of high‐density lipoprotein (HDL) functionality for target‐lesion revascularization in patients treated with coronary stents using a rapid cell‐free assay system to evaluate the functional capacity of HDL to accept additional cholesterol (cholesterol‐uptake capacity; CUC). Methods and Results From an optical coherence tomography (OCT) registry of patients treated with coronary stents, 207 patients were enrolled and their HDL was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A large and growing body of cohort studies has investigated the cholesterol efflux capacity of HDL using ABCA1 up‐regulated cells 10,11,21 . A single‐cohort study exists in which Nagano et al have described the importance of HDL functionality for targeting coronary lesion revascularization within patients who were treated with coronary stents using a cell‐free assay 15 . Their result demonstrates that CUC at follow‐up optical coherence tomography (OCT) was significantly lower in a group who developed neo‐atherosclerosis (NA+) compared to NA‐ group (Log Rank p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large and growing body of cohort studies has investigated the cholesterol efflux capacity of HDL using ABCA1 up‐regulated cells 10,11,21 . A single‐cohort study exists in which Nagano et al have described the importance of HDL functionality for targeting coronary lesion revascularization within patients who were treated with coronary stents using a cell‐free assay 15 . Their result demonstrates that CUC at follow‐up optical coherence tomography (OCT) was significantly lower in a group who developed neo‐atherosclerosis (NA+) compared to NA‐ group (Log Rank p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cholesterol uptake capacity (CUC) is a newly developed cell‐free, sensitive, and high‐throughput assay that reflects the functionality of HDL without using radio‐isotope labelling and cells 14 . Toh et al (2019) evaluated HDL function through the cell‐free CUC method in patients treated with coronary stents, mentioned that impaired HDL function might anticipate stent failure 15 . The research has tended to focus on qualitative rather than a quantitative assessment of HDL to improve the prediction of cardiovascular and atherosclerosis clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that serum CUC was highly correlated with HDL-C concentrations, indicating that the amount of HDL is a major determinant of CUC. Conversely, although CUC showed a significant inverse association with CAD, no such relationship could be demonstrated for HDL-C. We previously reported similar findings, [16][17][18]20 suggesting that functional assessment of HDL by CUC has more important clinical implications than quantitative HDL measurement.…”
Section: Factors Associated With Cadmentioning
confidence: 57%
“…Current smoking, renal insufficiency, ACE (angiotensin-converting enzyme) inhibitor or angiotensin II receptor blocker use, poor lipid profile, high-sensitivity C-reactive protein, underlying lipid-rich plaque, longer duration from stent implantation, or stent type have been associated with neoatherosclerosis. [3][4][5][6][7][8][9][10][11] The prevalence of neoatherosclerosis in the current study including only restenotic second-generation DES was 28.5% (146/512) with a median time from implantation to ISR of 2.8 (1.1-5.2) years. In autopsy cases studied a median of 2 years from DES implantation, Mori et al 16 showed lower prevalence of neoatherosclerosis (fibroatheroma) in cobalt-chromium everolimus-eluting stents (20%) compared with stainless steel sirolimus-eluting stents (41%).…”
Section: Discussionmentioning
confidence: 99%